The Use of Role-Play Methods to Improve Assertiveness Skills in Early Childhood Education at Al-Hidayah Kindergarten - Nurul Hidayah; Pascalian Hadi Pradana; Ahmad Afandi (Electronic Journal of Education, Social Economics and Technology, 2025)
The purpose of this study is to improve the assertiveness skills of early childhood children through the application of role-playing methods in the Al-Hidayah Playgroup (KB). Through role-playing activities designed with themes close to the children's experiences, it is hoped that children can be more confident in communicating and demonstrating assertive behavior appropriate to their developmental stages. The research method used in this study is Classroom Action Research (CAR). This research was conducted in two cycles, where each cycle consists of four stages, namely planning, acting, observing, and reflecting. Based on the results of the research in the two learning cycles, there was a significant increase in the development of children's assertiveness skills in KB Al-Hidayah. In the first cycle, although the role-playing activity with the theme "My Choice Today" had been implemented with careful planning, most children still had difficulty in expressing their opinions, feelings, and desires openly and politely. Only 26.67% of children were in the Developing According to Expectations (BSH) category, while the majority were still in the Starting to Develop and Not Yet Developing categories. In the second cycle, children demonstrated better assertiveness development through an improved approach using the theme "I Like, I Don't Like" which places more emphasis on expressing personal feelings. Observations showed that 93.3% of children had reached the minimum BSH category, and 40% of them were in the Very Well Developed (BSB) category. Thus, learning using the role-playing method has proven effective in improving assertiveness skills in early childhood at KB Al-Hidayah, and indicators of learning success have been achieved in the second cycle.